Painting Wonder : How Pauline Baynes Illustrated the World's of C.S. Lewis & J.R.R. Tolkien - Schon, K. W. (Katie Wray) (Spokane, WA : Waxwing Books, 2025)
"A picture book biography of Pauline Baynes, the artist whose illustrations brought the worlds of C.S. Lewis and J.R.R. Tolkien to life"--
Includes bibliographical references.
Keywords: Baynes, Pauline -- Juvenile literature; Tolkien, J. R. R. -- 1892-1973 -- Juvenile literature; Lewis, C. S. -- 1898-1963 -- Juvenile literature; Baynes, Pauline; Tolkien, J. R. R. -- 1892-1973.; Lewis, C. S. -- 1898-1963.; Women illustrators -- Biography -- England; Fantasy literature, English -- Juvenile literature; Illustrators; Women -- Biography; Biographies; Picture books